Experimental and theoretical research of continuous motion of rotor on anisotropic gapped elastic support - A. N. Nikiforov; G. Ya. Panovko; A. Ye. Shokhin (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2019)
Kinematic and dynamic features of flexible rotor rolling of an unlubricated uneven-stiffness gapped support are shown with the help of a theoretical model and full-scale tests. A combination of original approaches and well-known analytical and experimental methods is used. In particular, the motion equations are Lagrangian, derived in complex and complex-conjugate coordinates, and their solutions are sought in the exponential form, by excluding contact forces from consideration and by introducing a small parameter. Vibration measurements are not made on the rig frame using accelerometers, but at the source of vibration, i.e. by direct tracking of the rotor axle by a pair of eddy-current contactless displacement sensors installed in a XY configuration. Hence, the preciseness of the experimental data does not depend on the mechanical conductivity of the parts between the source rotor and the receiver sensors. As a result, the frequency, amplitude and existence domain of retrograde precession are reliably determined, and a conclusion is drawn that rolling under a certain combination of parameters is impossible in principle.